2011
DOI: 10.1007/s12975-011-0125-x
|View full text |Cite
|
Sign up to set email alerts
|

Blood–Brain Barrier Pathophysiology in Traumatic Brain Injury

Abstract: The blood-brain barrier (BBB) is formed by tightly connected cerebrovascular endothelial cells, but its normal function also depends on paracrine interactions between the brain endothelium and closely located glia. There is a growing consensus that brain injury, whether it is ischemic, hemorrhagic, or traumatic, leads to dysfunction of the BBB. Changes in BBB function observed after injury are thought to contribute to the loss of neural tissue and to affect the response to neuroprotective drugs. New discoverie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
449
1
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 538 publications
(475 citation statements)
references
References 247 publications
(315 reference statements)
7
449
1
4
Order By: Relevance
“…Median total symptoms and symptom severity were 7.5 (IQR 5 -13) and 12.0 (IQR 5.3 -22.6), respectively, at the time of medical evaluation. At the time of blood sampling, the median total symptoms reported by athletes with SRC was 5 (IQR 4-11), and the median symptom severity was 8 (IQR [4][5][6][7][8][9][10][11][12][13][14][15][16][17]. At the time of blood sampling, compared to healthy controls, athletes with SRC had significantly higher total symptoms scores (median score = 5.0 vs. 3.0 respectively; p = 0.04, data not shown) but not symptom severity scores.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…Median total symptoms and symptom severity were 7.5 (IQR 5 -13) and 12.0 (IQR 5.3 -22.6), respectively, at the time of medical evaluation. At the time of blood sampling, the median total symptoms reported by athletes with SRC was 5 (IQR 4-11), and the median symptom severity was 8 (IQR [4][5][6][7][8][9][10][11][12][13][14][15][16][17]. At the time of blood sampling, compared to healthy controls, athletes with SRC had significantly higher total symptoms scores (median score = 5.0 vs. 3.0 respectively; p = 0.04, data not shown) but not symptom severity scores.…”
Section: Resultsmentioning
confidence: 86%
“…An important component of this is identifying how and why certain molecules appear in the peripheral blood after injury. This requires a greater understanding of mechanisms involved in glymphatic clearance (18,(55)(56)(57), BBB disruption, and neuroendocrine dysfunction (17,19,21). In view of the latter, injury-induced alterations to hormones produced by both the sympathetic nervous system and hypothalamic-pituitary-adrenal (HPA)-axis can modulate peripheral immune function, altering blood levels of cytokines and chemokines (58)(59)(60).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In their study of traumatic brain injury induced by controlled cortical impact, Myer et al (2006) concluded that reactive astrocytes play essential protective roles, by preserving neural tissue and restricting inflammation after moderate brain injury. In the present study, a single HIFU exposure was sufficient to elicit an elevation in GFAP immunostaining in astrocytes, a characteristic neuro-immune response to blood-brain barrier cellular injury or infection (Abbott et al 2010;Chodobski et al 2011;Wolburg et al 2009). In this study, the animals were followed for only 24 h; a longer survival time is needed to establish the profile of astroglial activation.…”
Section: Discussionmentioning
confidence: 50%
“…This is followed by 161 two peaks of BBB opening at 4-6 hours and 2-3 days after the insult 162 (Chodobski et al 2011). Thus, though the extent and particular moments of 163 BBB permeability varies in the different pathologies, it can be used as a 164 therapeutic time-window to deliver molecules into the CNS (Rosenberg 2012).…”
Section: The Delivery Of Substances Across the Blood Cerebrospinal Flmentioning
confidence: 99%